2005
DOI: 10.1248/bpb.28.1668
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Saponins with the Inhibitory Effect on Nitric Oxide, Prostaglandin E2 and Tumor Necrosis Factor-.ALPHA. Production from Pleurospermum kamtschaticum

Abstract: Pleurospermum kamtschaticum HOFFMANN (Umbelliferae) is a perennial herb distributed in Kangwon province Korea.1)The aerial part of P. kamtschaticum are traditionally used to treat colds, arthritis, atherosclerosis and impotence.2) The constituents of P. kamtschaticum have not been reported though Luo et al. 3) reported on the isolation of saponins from another Pleurospermum spp. Activity-directed fractionation led to the isolation of the two saponins compounds 1 and 2 from P. kamtschaticum, which were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
(12 reference statements)
0
23
0
Order By: Relevance
“…PKE, including 0.93 g of buddlejasaponin IV/100 g PKE, was generously provided by Professor Hee-Jun Park, a coauthor of this work. 3) The following antibodies were purchased from the following sources: Bax, Bcl-2, procaspase-9, and horseradish peroxidase-conjugated secondary antibodies (Santa Cruz Biotechnology, Santa Cruz, CA); PARP and procaspase-3 (Cell Signaling Technology, Beverly, MA); NAG-1 (Upstate Biotechnology, Lake Placid, NY); and -actin (Sigma, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKE, including 0.93 g of buddlejasaponin IV/100 g PKE, was generously provided by Professor Hee-Jun Park, a coauthor of this work. 3) The following antibodies were purchased from the following sources: Bax, Bcl-2, procaspase-9, and horseradish peroxidase-conjugated secondary antibodies (Santa Cruz Biotechnology, Santa Cruz, CA); PARP and procaspase-3 (Cell Signaling Technology, Beverly, MA); NAG-1 (Upstate Biotechnology, Lake Placid, NY); and -actin (Sigma, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…2) Additionally, isolated buddlejasaponin IV evidenced potent anti-inflammatory activity, blocking the production of nitric oxide, prostaglandin E 2 , and tumor necrosis factor-in lipopolysaccharide-stimulated Raw 264.7 cells. 3) Colorectal cancer remains one of the most frequent malignant neoplasms worldwide. Epidemiological studies have suggested that the incidence and progression of colorectal cancer can be prevented by dietary factors, most notably a high intake of fruits and vegetables.…”
mentioning
confidence: 99%
“…During our on‐going screening program designed to identify the anti‐inflammatory potentials of natural compounds, we previously isolated buddlejasaponin IV from the aerial portion of Pleurospermum kamtschaticum by activity‐directed fractionation and characterized its structural identity spectroscopically ( 1 H and 13 NMR, IR, MS), as described previously (Jung et al ., 2005). P. kamtschaticum Hoffmann (Umbelliferae) is a perennial herb and is found in Kangwon province Korea (Koh & Jeon, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, saponin, a component of KKT, has been reported to reduce the level of TNF-a or prostaglandin E2, which is a key molecule involved in inflammatory pain. 14,15 These reports suggest that KKT might be beneficial in treating inflammation-related pain.…”
Section: Discussionmentioning
confidence: 99%